(untitled) (Homoeopathy for All, 2024)
The pancreas is an organ located behind the lower part of the stomach, in front of the spine and plays a vital role in diabetes. In type 1 diabetes, the beta cells of the pancreas no longer make insulin because the body’s immune system has attacked them. In type 2 diabetes, the pancreas loses the ability to secrete enough insulin in response to meals. Homoeopathy is considered as one of the very best alternative system for treating Diabetes Mellitus & its complications. This article reviews different complications of diabetes mellitus with general management and homoeopathic way of treatment.